2005
DOI: 10.1002/bjs.5171
|View full text |Cite
|
Sign up to set email alerts
|

Intra-anal and rectal application of l-erythro methoxamine gel increases anal resting pressure in healthy volunteers

Abstract: Intra-anal and rectal gel produced a sustained rise in MARP with rapid onset in volunteers. This raises the possibility of a therapeutic application for L-erythro methoxamine in patients with passive incontinence and internal anal sphincter dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
5
11
0
Order By: Relevance
“…These findings clearly place the interaction between noradrenergic and nitrergic nerves in the anal sphincter at the level of the smooth muscle, a suggestion consistent with the finding that exogenous noradrenaline reduced the magnitude of responses to both 1 Hz and 10 Hz EFS (Table 1). Taken together, our data is consistent with in vivo studies that demonstrate the ability α‐adrenoceptor antagonists to reduce resting anal sphincter pressure in the opossum and man 12–14 . The pathological significance of noradrenergic mechanisms in the anal sphincter is underlined by the report that botulinum toxin, which is successfully used for treating anal fissures, 25,26 can impair adrenergic contractions in the porcine isolated internal sphincter 27 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings clearly place the interaction between noradrenergic and nitrergic nerves in the anal sphincter at the level of the smooth muscle, a suggestion consistent with the finding that exogenous noradrenaline reduced the magnitude of responses to both 1 Hz and 10 Hz EFS (Table 1). Taken together, our data is consistent with in vivo studies that demonstrate the ability α‐adrenoceptor antagonists to reduce resting anal sphincter pressure in the opossum and man 12–14 . The pathological significance of noradrenergic mechanisms in the anal sphincter is underlined by the report that botulinum toxin, which is successfully used for treating anal fissures, 25,26 can impair adrenergic contractions in the porcine isolated internal sphincter 27 …”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, phentolamine‐sensitive neurogenic contractions have been noted in human 1,13 and sheep 3 isolated internal anal sphincter, when the dominant inhibitory effect of nitric oxide is removed using l ‐NAME. The importance of α‐adrenoceptors in sphincter tone is underlined by recent attempts to use L‐erythro‐methoxamine to elevate anal sphincter pressure 14 …”
mentioning
confidence: 99%
“…These results demonstrate that L ‐erythro methoxamine gel can produce a rapid, significant rise in anal resting pressure in patients with incontinence, as has been shown previously in human volunteers26. At the lowest concentration examined, the MARP was increased to within the normal range in four patients.…”
Section: Discussionsupporting
confidence: 87%
“…Methoxamine is a highly selective α 1 agonist, with almost no action at α 2 or β adrenoceptors25, and does not gain access to the central nervous system. Intra‐anal L ‐erythro methoxamine gel has been shown to produce a sustained rise in anal resting pressure in healthy volunteers26. These findings support the concept that anal sphincter tone may be manipulated pharmacologically using L ‐erythro methoxamine in patients with faecal incontinence.…”
Section: Introductionsupporting
confidence: 62%
“…NRL001, the 1R,2S stereoisomer of methoxamine hydrochloride, is a highly selective agonist for the a 1 -adrenoceptor. The 1R,2S methoxamine stereoisomer was four times more potent than phenylephrine as a constrictor agent in the porcine isolated IAS in vitro [3], and NRL001 is more potent at increasing anal sphincter tone compared with the other three methoxamine enantiomers and the racemic mixture methoxamine [4]. A single-dose exposure study using NRL001 suppositories in healthy volunteers demonstrated a clear increase in mean anal resting pressure (MARP) following administration of NRL001 in the absence of clinically noteworthy systemic adrenergic events [5].…”
Section: Introductionmentioning
confidence: 99%